Design of sewage treatment plan: using 'Biotreat' model / Kamal Baharin Saidin and Mohamad Fakri Abd Rahman - Saidin, Kamal Baharin; Abd. Rahman, Mohamad Fakri (1985)
The main object of researched on waste treatment is to control and reduce the environmental pollution. It is important that the methods evolved are within the economic means of the community served.